Tax planning and compliance for tax-exempt organizations : rules, checklists, procedures - Blazek, Jody (Wiley nonprofit authority series., 2020)
"Filled with practical tips and suggestions for handling such critical situations as preparing for and surviving an IRS examination, Tax Planning and Compliance for Tax-Exempt Organizations, Fifth Edition provides guidance for the significant issues facing nonprofit organizations. This book is an indispensable guide to navigating the complex maze of nonprofit tax rules and regulations. A clear and fully cited description of the requirements for the various categories of tax-exempt entities from public charities, private foundations, civic associations, business leagues, and social clubs to title-holding companies and governmental entities can be found. Practical guidance on potential for income tax on revenue-producing enterprises along with explanations of many exceptions to taxability is provided. Issues raised by Internet activity, advertising, publishing, providing services, and much more are explained"--